Disintegrable NIR light triggered gold nanorods supported liposomal nanohybrids for cancer theranostics - Chauhan, Deepak S.; Prasad, Rajendra; Devrukhkar, Janhavi; Selvaraj, Kaliaperumal; Srivastava, Rohit (Bioconjugate Chemistry, 2018)
In this work, facile synthesis and application of targeted, dual therapeutic gold nanorods-liposome (GNR-Lipos) nanohybrid for imaging guided photothermal therapy and chemotherapy is investigated. The dual therapeutic GNR-Lipos nanohybrid consists of GNR supported, and doxorubicin (DOX) loaded liposome. GNRs not only serve as a photothermal agent and increase the drug release in intracellular environment of cancer cells, but also provide mechanical strength to liposomes by being decorated both inside and outside of bilayer surfaces. The designed nanohybrid shows a remarkable response for synergistic chemophotothermal therapy compared to only chemotherapy or photothermal therapy. The NIR response, efficient uptake by the cells, disintegration of GNR-Lipos nanohybrid, and synergistic therapeutic effect of photothermal and chemotherapy over breast cancer cells MDA-MB-231 are studied for the better development of a biocompatible nanomaterial based multifunctional cancer theranostic agent.